Association of tumor mutational burden with genomic alterations in Chinese urothelial carcinoma. Issue 3 (2nd November 2021) - Chen, Xusheng; Ou, Zhenyu; Wang, Lei; Zhang, Zhenting; Fan, Xiaodong; Liu, Huanhuan; Wang, Wenping; Zhang, Yanrui; Zhu, Jun; Liang, Xiayuan; Lou, Feng; Cao, Shanbo; et al.
Abstract: The tumor mutational burden (TMB) calculated by whole‐exome sequencing (WES) is a promising biomarker for the response to immune checkpoint inhibition (ICIs) in solid tumors. However, WES is not feasible in the routine clinical setting. In addition, the characteristics of the TMB in Chinese urothelial carcinoma (UC) are unclear. The aim of this study was to demonstrate the reliability of an Acornmed 808 panel and analyze the characteristics of the TMB in Chinese UC. An Acornmed 808 panel was designed and virtually validated using UC data from the cancer genome atlas (TCGA). Comprehensive analysis of sequencing and clinical data was performed to explore the characteristics of the TMB for 143 Chinese UC patients. Compared to the TMB calculated with random 808‐, 500‐, and 250‐gene panels, the TMB calculated with the Acornmed 808 panel was closer to that calculated by WES. There were marked disparities in the mutational landscape and TMB between Chinese and TCGA UC data. The TMB was negatively associated with copy number variation (CNV). In contrast, the TMB was positive correlation with numbers of mutated DDR genes. Exposure to aristolochic acid signature was observed only in the TMB‐high groups. The Acornmed 808 panel is a clinically practical method to assess the TMB. The TMB was associated with the DDR gene status and CNV counts and might be a biomarker for further stratification of UC patients. The study suggested that patients with high TMB may have a unique carcinogenic mechanism.